Early and Sustained Supramarginal Gyrus Contributions to Phonological Processing - Sliwinska, Magdalena Wiktoria W.; Khadilkar, Manali; Campbell-Ratcliffe, Jonathon; Quevenco, Frances; Devlin, Joseph T. (Frontiers in Psychology, 2012)
Reading is a surprisingly difficult task that, at a minimum, requires recognizing a visual stimulus and linking it with its corresponding sound and meaning. Neurologically, this involves an anatomically distributed set of brain regions cooperating to solve the problem. It has been hypothesized that the supramarginal gyrus (SMG) contributes preferentially to phonological aspects of word processing and thus plays an important role in visual word recognition. Here, we used chronometric transcranial magnetic stimulation (TMS) to investigate the functional specificity and timing of SMG involvement in reading visually presented words. Participants performed tasks designed to focus on either the phonological, semantic, or visual aspects of written words while double pulses of TMS (delivered 40 msec apart) were used to temporarily interfere with neural information processing in the left SMG at five different time windows. Stimulation at 80/120, 120/160 and 160/200 msec post-stimulus onset significantly slowed subjects’ reaction times in the phonological task. This inhibitory effect was specific to the phonological condition, with no effect of TMS in the semantic or visual tasks, consistent with claims that SMG contributes preferentially to phonological aspects of word processing. The fact that the effect began within 80–120 msec of the onset of the stimulus and continued for approximately 100 msec, indicates that phonological processing initiates early and is sustained over time. These findings are consistent with accounts of visual word recognition that posit parallel activation of orthographic, phonological and semantic information that interact over time to settle into a distributed, but stable, representation of a word.